An anatomy of central bank{u2019}s supervisory functions with special reference to Bangladesh Bank - Masum, Imtiaz Ahmad; Venkatesh, Sundar; Juthathip Jongwanich; Badir, Yuosre; Bangladesh Bank (Pathumthani : Asian Institute of Technology, 2012)
In the early days the main functions of commercial bank were to collect deposit and extend credit. But now-a-days the functions of bank have become more complex and manifold. The role of the central bank as the supervisory authority is also increasing alongside the increasing functions of commercial banks. The development of a country is mainly dependent on a well developed banking system and so the role of Bangladesh Bank (the central bank of Bangladesh) is getting much more importance day by day. In Bangladesh, Bangladesh Bank is the sole authority to supervise the banks and the banks are supposed to obey Bangladesh Bank regulation and supervisory guidelines. In this context, the various approaches to bank supervision, the coverage of bank supervision and the modes of bank supervision have been discussed. I have endeavored to find out the various supervisory issues prevalent in the G-7 countries and Risk Based Supervision also been pointed out.
The Basle Agreement on bank supervision is the internationally practiced standard for the banking supervision. Bank supervision by Bangladesh Bank is in line with Basle core principles. To measure the health of a bank it is much more important and the CAMELS rating system is the internationally approved rating system for the banks. But due to the increasing risk of failure in the banking system, only the supervisory guidelines are not sufficient to ensure a healthy banking system. Developed countries now-a-days following a new method called Risk Based Supervision. It is also discussed. On the other hand, in the wake of recent global financial crisis we have seen series of bank failure. The causes and effect of bank failure is also discussed.
A project submitted in partial fulfillment of the requirements for the degree of Professional Master in Banking and Finance, School of Management
Keywords: Bangladesh Bank -- Management; Banks and banking